EXPERIENTIAL FUNCTION IN DONALD TRUMP’S SPEECH ABOUT RADICAL ISLAMIC TERRORISM - Halimatun Husna Rambe; Siti Aisyah Ginting; Amrin Saragih (Universitas Negeri Medan, 2018)
This study deals with the Experiential Function in Donald Trump’s Speech about Radical Islamic Terrorism. This study attempted to investigate the dominant elements of experiential function used in the speech, the realization and the reasons why the elements of experiential function are coded in the speech. This study was conducted by using qualitative design. The data in this study were the utterances of Donald Trump’s speech transcribed in written mode. The speech is campaign speech about Radical Islamic Terrorism on August 15th, 2016 at Youngstown State University. The research findings show that the dominant process found in the speech was material process, the dominant participant was actor and goal, and the dominant circumstance was location spatial and temporal. The processes were realized congruently and incongruently in metaphorical wording. Material process is dominantly used by Donald Trump about terrorism because he wanted to show the evil deeds done by terrorist and stimulate the listeners for future actions against terrorism, actor and goal participants show two confronting parties and circumstance location spatial and temporal show his point of view is authentic and objective. Keywords: Experiential Function, Speech, Terrorism